PEMECAHAN SAHAM TERHADAP LIKUIDITAS DAN RETURN SAHAM - ELLEN RUSLIATI; ESTI NUR FARIDA (Jurnal Bisnis dan Akuntansi, 2010)
Number of demand for shares will raise the price and share return. Some companies choose to do share split because the prices are too high that will affect investor interest. The share split is the corporate action to make its share price lower and more attractive to be traded. The method used is descriptive and verification method. Data analysis used is event study of the announcement of a corporate action. Populations are 30 companies that make share split from 2006 until 2008 in Indonesia Share Exchange. The analysis was performed by using paired samples t test to test the average difference. The result shows the bid-ask spread before and after share split are different, meaning that share split affects the liquidity of shares, but objective to improve the share liquidity is not achieved. Abnormal returns before and after share split are different, meaning that share split affects the share return, but objective to improve the share return is not achieved.